Flexible and transparent films produced from cellulose nanowhisker reinforced agarose. (15th August 2018) - Felfel, Reda M.; Hossain, Kazi M. Zakir; Kabir, Sumaya F.; Liew, Soon Y.; Ahmed, Ifty; Grant, David M.
Highlights: Never-dried CNWs and Agarose were utilised to produce transparent and flexible nanocomposite films. The nanocomposites films maintained more than 84% optical transparency. The crystallinity of the nanocomposite films increased with the addition of CNWs. A significant increase in mechanical and thermomechanical properties of the nanocomposites was obtained. Incorporation of CNWs led to reduction in the swelling rate of the nanocomposite. Abstract: Transparent and flexible nanocomposite films with a range of Agarose to Cellulose Nano-Whisker (CNW) ratios were produced using never-dried CNWs. The incorporation of never-dried CNWs within Agarose played an important role in the surface roughness (Ra 7–15 nm) and light transparency of the films (from 84 to 90%). Surface induced crystallisation of Agarose by CNWs was also found with increasing percentage of crystallinity (up to 79%) for the nanocomposite films, where CNW acted as nucleating sites. The enhanced tensile strength (ca. 30% increase) and modulus (ca. 90% increase) properties of the nanocomposite films compared to the control Agarose film indicated the effectiveness of the nanowhiskers incorporation. The storage modulus of the nanocomposite films increased also to be tripled Agarose alone as the CNWs content reached 43%. The swelling kinetics of the nanocomposites revealed that addition of CNWs reduced the long-term swelling capacity and swelling rate of the nanocomposite.